(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aimed at identifying the effectiveness of the use of the programmed learning strategy in the light of the sustainable educational process. The researcher applied the experimental method; the study population consisted of (60) male students of the Faculty of Physical Education and Sports Science, at the Hashemite University; and the sample comprised (48) male students enlisted in the physical education teaching methods course. The sample was randomly divided into two equal groups: control group students who were taught using the traditional learning strategy, and the experimental group students who were taught using the programmed learning strategy. The instrument consisted of the programmed learning program, and SPSS was applied. The reliability coefficient of the educational program amounted (0.86). The results indicated statistically significant differences between the results of the post-test of the experimental and control groups in the performance of the front rolling, rear rolling, human acceleration and standing on the head skills, in favor of the experimental group. The researcher set out a number of recommendations, most important of which underscored the need to encourage teaching the floor movements in gymnastics by programmed learning for both sexes and different ages. This is due to the speed of learning, saving time and effort, taking into account individual differences, and providing the factor of excitement and suspense for the learner.